TRAF5 Is a Downstream Target of MAVS in Antiviral Innate Immune Signaling - Tang, Eric D. (Public Library of Science, 2010)
The recognition of nucleic acids by the innate immune system during viral infection results in the production of type I interferons and the activation of antiviral immune responses. The RNA helicases RIG-I and MDA-5 recognize distinct types of cytosolic RNA species and signal through the mitochondrial protein MAVS to stimulate the phosphorylation and activation of the transcription factors IRF3 and IRF7, thereby inducing type I interferon expression. Alternatively, the activation of NF-κB leads to proinflammatory cytokine production. The function of MAVS is dependent on both its C-terminal transmembrane (TM) domain and N-terminal caspase recruitment domain (CARD). The TM domain mediates MAVS dimerization in response to viral RNA, allowing the CARD to bind to and activate the downstream effector TRAF3. Notably, dimerization of the MAVS CARD alone is sufficient to activate IRF3, IRF7, and NF-κB. However, TRAF3-deficient cells display only a partial reduction in interferon production in response to RNA virus infection and are not defective in NF-κB activation. Here we find that the related ubiquitin ligase TRAF5 is a downstream target of MAVS that mediates both IRF3 and NF-κB activation. The TM domain of MAVS allows it to dimerize and thereby associate with TRAF5 and induce its ubiquitination in a CARD-dependent manner. Also, NEMO is recruited to the dimerized MAVS CARD domain in a TRAF3 and TRAF5-dependent manner. Thus, our findings reveal a possible function for TRAF5 in mediating the activation of IRF3 and NF-κB downstream of MAVS through the recruitment of NEMO. TRAF5 may be a key molecule in the innate response against viral infection.